2005
DOI: 10.1021/jp053633e
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the Role of Size-Extensive Normalization for Multireference Coupled Cluster (MRCC) Theory Using General Model Space:  A Valence Universal MRCC Approach

Abstract: We present a brief description of a valence-universal multireference coupled cluster (VU-MRCC) theory that can handle completely general incomplete model spaces, remaining close to the intermediate normalization (IN) condition for omega as much as possible without violating extensivity and without the use of a post facto correction. In this formalism, the connectedness of the cluster operators as well as effective Hamiltonian and hence the extensivity of the corresponding roots is achieved by invoking appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…To get around this difficulty Bera et al [81] suggested quite an intricate combinatoric analysis which in our opinion is really not necessary to arrive at a connected H eff . There is in fact much simpler and straightforward way to formulate the problem where the normal ordered Ansatz for X is replaced by a new Ansatz and no counter-term is needed at all.…”
Section: Imposition Of X Cl ¼ 1 Cl and Size-extensivity Of H Effmentioning
confidence: 97%
See 4 more Smart Citations
“…To get around this difficulty Bera et al [81] suggested quite an intricate combinatoric analysis which in our opinion is really not necessary to arrive at a connected H eff . There is in fact much simpler and straightforward way to formulate the problem where the normal ordered Ansatz for X is replaced by a new Ansatz and no counter-term is needed at all.…”
Section: Imposition Of X Cl ¼ 1 Cl and Size-extensivity Of H Effmentioning
confidence: 97%
“…This analysis is important in the sense that it indicates how a new Ansatz for X without the use of the closed operator X cl leads in a straight forward manner to a new H eff which is related by a similarity transformation to the one formulated by Bera et al [81]and at the same time ensures X cl ¼ 1 cl . The latter formulation will be presented in Section 3.…”
Section: Imposition Of X Cl ¼ 1 Cl and Size-extensivity Of H Effmentioning
confidence: 98%
See 3 more Smart Citations